Comparison of Morbidity and Mortality in Patients with Jejunoileal Perforation presented before and after 24 hours in Surgery Department - Bugti , Muhammad Hanif; Ahmed Qureshi, Shoaib; Zarkoon, Rehan; Abdullah,; Syed Abdul Nasir,; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2024)
Background: Jejunoileal perforations are critical conditions that can lead to significant morbidity and mortality. Timely intervention is essential to prevent complications and improve patient outcomes. Objective: This study aims to compare the morbidity and mortality rates of patients with jejunoileal perforations who presented within 24 hours of symptom onset versus those who presented after 24 hours in the surgery department of Bolan Medical Complex, Quetta. It seeks to evaluate the impact of delayed presentation on surgical outcomes. Methods: A qualitative approach was employed, involving semi-structured interviews and patient record reviews for 120 patients diagnosed with jejunoileal perforation. The participants were divided into two groups: Group A (presented within 24 hours) and Group B (presented after 24 hours). Data were analyzed thematically to identify differences in morbidity, mortality, and recovery experiences. Results: The findings reveal that patients in Group A exhibited significantly lower morbidity and mortality rates compared to those in Group B. Complications were noted in 30% of cases in Group B, whereas only 10% of patients in Group A experienced complications. The average hospital stay was longer for Group B, averaging 7 days compared to 3 days for Group A. Conclusion: Early presentation and surgical intervention in jejunoileal perforations are crucial for reducing morbidity and mortality. The study underscores the importance of timely medical attention in improving surgical outcomes and enhancing patient recovery.